Molecular basis for stratum corneum maturation and moisturization. (1st September 2014) - Rawlings, A.V.
Summary: This themed edition of BJD is dedicated to the work of Professor Ronald Marks for his untiring work on the understanding of stratum corneum (SC) structure and function. He and his coworkers, in my opinion, had the right focus for cosmetic dermatology issues. Namely, consumers experience the wonderful properties of the SC through sight, touch and the somatosensory system. They do not experience, for example, transepidermal water loss and skin conductance or capacitance! Marks understood this and set about developing the methodologies to examine the changes in SC architecture and function when desquamation goes haywire. More importantly, he understood that moisturizers do far more than simply hydrate the SC, as exemplified in the paper by Tree and Marks, 'An explanation for the placebo effect of bland ointment bases.'1 Moisturizing ingredients influence the properties of the SC in many ways with the sole purpose of overcoming the signs and symptoms of dry skin. Marks demonstrated the decrease in SC cohesion following use of hydrating agents, which led to the mechanistic work on the effects of a simple molecule like glycerol on the desquamatory process. In further exploiting forced desquamation and use of abrasion, he showed that improvements in exfoliation contribute to the mitigation of the signs of photodamaged skin, which can explain part of the antiageing effect of simple moisturizers. It is here that I should point out that at least this particular author in 1988 was 'standing on the shoulders of' a great corneologist whose work influenced his research directions. So this paper will provide an update on the latest developments for the molecular basis of SC maturation and moisturization, while highlighting the contributions of Professor Marks in the different areas.